Experimental and simulation research on the screening effect of the pixelated CZT imaging detector. (July 2018) - Li, Miao; Zha, Gangqiang; Zhou, Benjie; Ma, Yuedong; Xiao, Shali; Zhao, Mingkun; Ding, Keyu; Zhou, Shousen
Abstract: Massive efforts have been made to investigate the characteristics of the CdZnTe detector under different extreme conditions. In this paper, we experimented with different radiation sources to investigate the imaging screening effect of the pixelated CdZnTe detector under ultrahigh irradiance. A donut-shaped irradiation image was obtained due to the increase in the X-ray tube current or the tube voltage. Moreover, statistical data revealed that the total count of all pixels was not significantly different, while the event-count of irradiated area pixels decreased significantly. A consequence of the screening effect was that the event counts redistributed among pixels that are located in the irradiated area, while the inner electric field was distorted. This leads to the catastrophic performance degradation of the central pixels. According to the Poisson equation, we developed a theoretical model of the CdZnTe detector using the finite element software COMSOL to enable an in-depth investigation of carrier collection in the CdZnTe crystal. A comparison between the simulations and the test results showed that pixels in the central irradiated area are completely screened under the ultrahigh irradiance because of the emergence of the relatively higher potential region, which can distort the electron drift path. Furthermore, the photon-generated signal can be collected only partly at the edge of the irradiated area, which was relatively stable because the collection area in the CdZnTe volume was relatively limited. The imaging results deduced from the simulations are well consistent with the experimental data. Highlights: Donut-shaped irradiation images were obtained with different irradiation sources. It was revealed that the total event count of all pixels was not significantly different, while the event count of irradiated area pixels decreased significantly. Comsol model was developed to enable an in-depth research of carrier collection. The counts actually redistributed among pixels at the edge of irradiated area. Limited collection area makes detector signal relatively stable in screening effect.